THE CORRELATION OF SLEEP QUALITY WITH DRY EYE DISEASE (DED) IN RURAL AREAS - Redjeki, Daniela Pauline; Dewi, Debby Shintiya; Aldina, Rosy (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2026)
Background: Dry Eye Disease (DED) is a multifactorial ocular condition characterized by tear film instability and ocular surface inflammation. The severity of DED is closely related with poorer quality of life. Studies showed that poor sleep quality occurs in more than 40% of patients with DED. This is due to decreased tear secretion and increased tear osmolarity due to poor sleep. Sleep deprivation is associated with higher risk of diseases that have been shown to be associated with an increased risk of dry eye. Objective: This study was conducted to find the relationship between sleep quality and dry eye disease in Indonesia. Methods: This study was an analytic observational study using a cross sectional study design on 240 respondents in Mendalanwangi Village, Wagir District, Malang Regency. The study was conducted by examining Fluorescein TBUT and filling out the DEQ-5 questionnaire to assess DED and the PSQI questionnaire to assess sleep quality among the study subjects. Results: Among participants who experienced DED, 63.9% reported poor sleep quality, whereas only 36.1% reported good sleep quality. Conversely, in the non-DED group, 56.7% had good sleep quality while 43.3% had poor sleep quality. The results of statistical analysis using the chi-square test with a significance value of p = 0.003 (p < 0.05) and OR 2.31 which indicates there is an association between sleep quality and DED. Conclusion: Poor sleep quality increases the risk of DED 2.3 times compared to good sleep quality and affecting person's quality of life, hence increasing morbidity and mortality.